A dual-doped modified self-repairing self-warning protective coating and a preparation method thereof

CN119570333BActive Publication Date: 2026-10-27WUXI POWER SUPPLY BRANCH OF STATE GRID JIANGSU ELECTRIC POWER CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411782030.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2026-10-27
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

但该现有技术文件的不足之处在于涂层只能通过提高阴极保护,由于活化锌数目的增多,会导致锌消耗过快进而使涂层的寿命变短,同时,也无法通过直截了当地通过涂层表面判定基体的腐蚀程度进而无法实现材料防护失效预警

Benefits of technology

[0013]有益效果: 本发明的银杏叶提取物和稀土配合物双掺改性自修复自预警防护涂层与一般的防护涂料相比,具有更优异的耐蚀性能;涂层内部水性富锌涂层与EGB-LDH结合,当内部基体产生腐蚀时,外部LDH将EGB进行释放,进而促进钢基体内部形成耐蚀钝化膜,提高基体自身的自修复能力;涂层外部利用低表面处理环氧耐磨涂层自身的高致密性、耐磨性和抗渗性,对其所覆盖的EGB-LDH水性富锌涂层提供高效防护;镧系金属有机发光材料对结构内部的Fe3+响应比较灵敏。正是利用了这一特性,当涂层所保护的钢基体发生腐蚀后,Fe3+浓度升高,防护材料的荧光强度随之降低,从宏观的角度可通过发光强度的变化识别基体的腐蚀程度,无需更繁琐的检测设备与手段。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570333B_ABST
    Figure CN119570333B_ABST
Patent Text Reader

Abstract

The application discloses a double-doped modified self-repairing self-warning protective coating, which is composed of a modified water-based zinc-rich coating and a modified low-surface-energy coating, wherein the modified water-based zinc-rich coating is obtained by modifying a water-based zinc-rich coating with a hydrotalcite-ginkgo biloba extract, and the modified low-surface-energy coating is obtained by modifying a low-surface-energy coating with a lanthanide series rare earth organic material. Compared with general protective coatings, the ginkgo biloba extract and rare earth complex double-doped modified self-repairing self-warning protective coating has more excellent corrosion resistance; the lanthanide series metal organic luminescent material can emit light in response to the change of the Fe 3+ The response is sensitive, and the corrosion degree of the substrate can be recognized through the change of the light emission intensity from the macroscopic perspective without more complicated detection equipment and means.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of protective coatings, specifically relating to a dual-doped modified self-healing and self-early warning protective coating and its preparation method. Background Technology

[0002] Corrosion is a persistent problem in industrial production and infrastructure maintenance, posing a significant threat to the safety and lifespan of equipment. While corrosion is one of the most effective means of preventing corrosion, ordinary coating systems offer poor corrosion resistance and short-term protection. With the development of anti-corrosion coating technology, heavy-duty anti-corrosion coatings are increasingly being used in engineering equipment protection. Heavy-duty anti-corrosion coatings are high-performance coatings that provide long-term protection in harsh corrosive environments. Commonly used coatings include polyurethane coatings, epoxy resin coatings, rubber coatings, and zinc-rich coatings. They typically consist of a primer, intermediate coat, and topcoat, with a film thickness exceeding 200 µm. The overall effect of this coating can last for over 15 years. Zinc-rich coatings, as a common anti-corrosion coating, are widely used in various corrosive environments due to their ease of application and excellent corrosion resistance, becoming a primary means of protecting engineering facilities. Among them, water-based zinc-rich coatings are highly regarded for their low volatile organic compound content and environmentally friendly characteristics.

[0003] Current methods for zinc-rich protective coatings include doping with carbon nanomaterials to enhance their cathodic protection performance. Existing technical literature (CN 117070123 A) proposes a solvent-based zinc-rich heavy-duty anti-corrosion coating. The components, including flake zinc powder, graphene oxide, flake Mxene, and flake basalt, are all modified to improve the coating's compatibility and dispersibility, effectively preventing delamination after application. Flake Mxene and graphene oxide, as nanoscale fillers, improve the coating's density. Furthermore, flake Mxene and graphene oxide can alter the coating's spatial structure, extending the corrosion path and increasing the area of ​​the protective layer within the film, giving the slurry thixotropic properties and reducing the amount of solvent required, thus lowering the VOC content of the coating. Additionally, flake basalt is an inert filler with low oil absorption, reducing the need for epoxy resin and increasing the solids content of the dry film. Ultrafine flake-shaped zinc powder provides corrosion protection due to its cathodic protection effect. Simultaneously, the flake-like structure of the zinc powder creates a complex internal structure in the coating, delaying the intrusion of corrosive media and further enhancing the coating's corrosion resistance. Using mixed active solvents instead of common organic solvents, these solvents exhibit reactivity and can participate in the curing reaction of epoxy resin, becoming part of the epoxy resin crosslinking network. Therefore, compared to volatile solvents, this reduces solvent evaporation, lowers the VOC content of the coating, and allows for faster curing. However, the limitations of this prior art are that the coating can only improve cathodic protection. The increased number of activated zinc particles leads to excessive zinc consumption, shortening the coating's lifespan. Furthermore, it cannot directly assess the degree of substrate corrosion through the coating surface, thus failing to provide early warning of material protection failure.

[0004] Low surface energy coatings, also known as non-stick coatings, are a rapidly developing type of coating system in recent years. They are typically composed of fluorocarbon resins, silicone resins, polytetrafluoroethylene powder, and special modified materials. Low surface energy coatings exhibit good adhesion to the substrate and a contact angle with pure water >120°. With the increasing maturity of room-temperature curing fluorocarbon resin coatings that offer ease of use and excellent overall performance such as resistance to atmospheric aging, the applications of low surface energy coatings are constantly expanding. They play an important role in marine engineering, national defense, friction reduction, anti-fouling, and winter sports. Two-component, polyamine-cured low-surface-treatment epoxy coatings feature low surface treatment requirements, wear resistance, and high solids content. They are specifically designed for areas where ideal surface treatment is not possible or necessary. They provide long-term corrosion protection in highly corrosive environments and can be used as primers, intermediate coats, topcoats, or single coats in atmospheric and immersion environments. They are suitable for properly treated carbon steel, galvanized steel, stainless steel, aluminum, concrete, and many aged coated surfaces, and can be applied at surface temperatures below 0°C. Summary of the Invention

[0005] Purpose of the invention: The purpose of this invention is to address the shortcomings of existing technologies by providing a self-healing and self-early warning protective coating modified by dual doping of Ginkgo biloba extract and rare earth complexes, and its preparation method. The invention involves modifying a water-based zinc-rich coating with hydrotalcite-Ginkgo biloba extract (EGB-LDH), modifying a low-surface-treatment epoxy wear-resistant coating with lanthanide rare earth organic materials, and then combining the modified low-surface-treatment coating with the zinc-rich coating to obtain the dual-doping modified self-healing and self-early warning protective coating of this invention.

[0006] Technical solution: The dual-doped modified self-healing and self-early warning protective coating of the present invention is composed of a modified water-based zinc-rich coating and a modified low surface energy coating. The modified water-based zinc-rich coating is obtained by modifying the water-based zinc-rich coating with hydrotalcite-ginkgo extract, and the modified low surface energy coating is obtained by modifying the low surface energy coating with lanthanide rare earth organic materials.

[0007] Preferably, the hydrotalcite-ginkgo extract has a weight content of 5% in the modified water-based zinc-rich coating, and the lanthanide rare earth organic material has a weight content of 5% in the modified low surface energy coating.

[0008] Preferably, the hydrotalcite-ginkgo extract (EGB-LDH) is prepared by reacting ginkgo leaf extract and hydrotalcite.

[0009] Preferably, the lanthanide rare earth organic material is prepared from europium hydrated nitrate, 1-10 phenanthroline, terephthalic acid, anhydrous ethanol and deionized water.

[0010] Preferably, the preparation method of EGB-LDH is as follows: calcined hydrotalcite is added to a solution containing ginkgo extract and sodium hydroxide, the mixture is stirred and the pH of the mixture is controlled to be stable at 10.5-11.5, the reaction is carried out at 50°C for 15-24 hours, filtered and washed until neutral, and dried to obtain hydrotalcite-ginkgo extract.

[0011] Preferably, the components and their contents in the modified water-based zinc-rich coating are expressed as weight percentages as follows: 1-Methoxy-2-propanol ≤10 Epoxy resin (MW700 - 1200) ≤5 Epoxy resin (MW<700) ≤5 γ-Propyltrioloxypropyltrimethylsilane <5 polyetheramine <10 EGB-LDH =5 Preferably, the components and their contents in the modified low surface energy coating are expressed as weight percentages as follows: Polymers of C18-unsaturated fatty acid dimers with 4,4'-(1-methylethylidene)bi(bis)phenol and chloromethyl ethylene oxide 10 Polymer of nut shell liquid and epichlorohydrin 10 xylene 10 Isobutanol 5 Methylstyrene 5 Styrified phenol 5 1-Butanol 30 Lanthanide rare earth organic light-emitting materials 5 This invention also provides the application of a dual-doped modified self-healing and self-early warning protective coating, comprising the following steps: 1) The modified water-based zinc-rich coating is sprayed onto the metal substrate using a spray gun and then dried; 2) Spray the modified low surface energy coating onto the modified water-based zinc-rich coating from step 1) that has already dried and then dry it.

[0012] The coating thickness of both the modified water-based zinc-rich coating and the modified low surface energy coating is 50-90µm.

[0013] Beneficial Effects: The self-healing and self-early warning protective coating modified by dual doping of Ginkgo biloba extract and rare earth complexes of this invention exhibits superior corrosion resistance compared to general protective coatings. The internal water-based zinc-rich coating is combined with EGB-LDH; when corrosion occurs in the internal substrate, the external LDH releases the EGB, thereby promoting the formation of a corrosion-resistant passivation film within the steel substrate and enhancing the substrate's self-healing ability. The external coating utilizes the high density, wear resistance, and impermeability of the low-surface-treatment epoxy wear-resistant coating to provide efficient protection for the EGB-LDH water-based zinc-rich coating it covers. The lanthanide metal organic light-emitting material provides protection for the Fe within the structure. 3+ The response is quite sensitive. It is precisely by utilizing this characteristic that, when the steel substrate protected by the coating corrodes, the Fe... 3+ As the concentration increases, the fluorescence intensity of the protective material decreases. From a macroscopic perspective, the degree of corrosion of the substrate can be identified by the change in luminescence intensity, without the need for more complicated detection equipment and methods. Attached Figure Description

[0014] Figure 1 This is the surface morphology (SEM) of the coating before and after full immersion corrosion in Example 5 of the present invention.

[0015] Figure 2 The surface morphology (SEM) of the basic water-based zinc-rich coating before and after full immersion corrosion is shown. Detailed Implementation

[0016] To enhance understanding of the present invention, the present invention will be further described in detail below with reference to embodiments and accompanying drawings. These embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.

[0017] Some of the raw materials used in the examples were derived from Rohn's reagent, europium nitrate hexahydrate, R003553. 1,10-Phenanthroline (Chinese Medicine) 1,10-Phenanthroline (Analytical Grade, GR Chemical Reagent) Rohn's reagent for terephthalic acid, R011713 CO3-LDH (synthetic hydrotalcite) Maclean's reagent, 11097-59-9 EGB Food Grade Ginkgo Leaf Extract and Ginkgo Flavonoid Powder Water-based zinc-rich coating: Jotun Coatings, Barrier 80 WF Low surface energy coating: Jotun Coatings, Jotamastic 90 Example 1: Preparation of Lanthanide Rare Earth Organic Light-Emitting Materials Europium nitrate hexahydrate, 1,10-phenanthroline (g), and terephthalic acid were weighed separately in anhydrous ethanol at a molar ratio of 1:2:1 and dissolved. The mixture was stirred in an 80°C water bath for 10 h, and then centrifuged three times at 5000 r / min. The resulting solution was placed in a reaction vessel and kept in an 80°C oven for 24 h to obtain lanthanide rare earth organic light-emitting material (Eu(PTA)). 1.5 phen).

[0018] Example 2 Preparation of EGB-LDH Commercial CO3-LDH was calcined in a muffle furnace at 400℃ / 450℃ / 500℃ / 550℃ for 3 hours using a calcination reduction method, and then cooled to room temperature to obtain calcined LDH (CLDH). Then, a 500 mL mixture of 0.25 mol / L EGB and 0.25 mol / L NaOH was prepared, and 2 g of CLDH was added to the mixture. During stirring, 2 mol / L NaOH solution was added dropwise to control the pH of the mixture, maintaining it at approximately 11. Nitrogen gas was then purged for 20 minutes, and the solution was sealed. The mixture was stirred in a 50℃ water bath for 15-24 hours. After stirring, the mixture was filtered, and the precipitate was washed with deionized water and anhydrous ethanol until neutral. Finally, it was dried at 60℃ to obtain EGB-LDH.

[0019] Example 3: Preparation of EGB-LDH modified waterborne zinc-rich protective coating Add the water-based zinc-rich coating (60wt% zinc powder, 10wt% 1-methoxy-2-propanol, 5wt% epoxy resin (MW700-1200), 5wt% epoxy resin (MW<700), 5wt% γ-propanetrioloxypropyltrimethylsilane, 10wt% polyetheramine) and 5wt% EDH-LDH to a mixer. Mix at 700-1000 r / min for 30 minutes until homogeneous. Immediately spray the mixed EGB-LDH modified water-based zinc-rich coating onto the steel substrate using a spray gun. Control the thickness of the EGB-LDH modified water-based zinc-rich coating to 50-90µm. Place the sprayed coating in an oven at 40℃ and dry for 2 hours.

[0020] Example 3-1 Preparation of EGB-LDH modified waterborne zinc-rich protective coating Add the water-based zinc-rich coating (70wt% zinc powder, 5wt% 1-methoxy-2-propanol, 5wt% epoxy resin (MW700-1200), 5wt% epoxy resin (MW<700), 5wt% γ-propanetrioloxypropyltrimethylsilane, 5wt% polyetheramine) and 5wt% EDH-LDH to a mixer. Stir at 700-1000 r / min for 30 minutes until the mixture is homogeneous. Immediately spray the mixed EGB-LDH modified water-based zinc-rich coating onto the steel substrate using a spray gun. Control the thickness of the EGB-LDH modified water-based zinc-rich coating to 50-90µm. Place the sprayed coating in an oven at 40℃ and dry for 2 hours.

[0021] Example 4: Preparation of low surface energy coating modified from lanthanide rare earth organic light-emitting materials A low surface energy coating is prepared by mixing the following components by weight percentage: 20 wt% epoxy resin (MW < 700), 10 wt% polymer of C18-unsaturated fatty acid dimer with 4,4'-(1-methylethylidene)bi(di)phenol and chloromethyl ethylene oxide, 10 wt% polymer of nut shell liquid with epichlorohydrin, 10 wt% xylene, 5 wt% isobutanol, 5 wt% methylstyrene, 5 wt% styrene, and 30 wt% 1-butanol in a mixer for 15-20 minutes. Alternatively, a low surface energy coating with the above component contents can be purchased.

[0022] Lanthanide rare earth organic light-emitting materials (Eu(PTA)) 1.5 Add 5wt% of phen to the dissolved anhydrous ethanol solution, then pour into a mixer and stir at 700-1000 r / min for 5-10 minutes until thoroughly mixed. Finally, combine the low surface energy coating with Eu(PTA). 1.5 After mixing with phen, slowly pour the mixture into a mixer and continue to stir rapidly for 15-20 minutes until homogeneous to obtain a lanthanide rare earth organic light-emitting material modified with a low surface energy coating.

[0023] Example 5: Application Method of Double-Doped Modified Self-Healing and Self-Earning Protective Coating The EGB-LDH waterborne zinc-rich coating prepared in Example 3 was sprayed onto a steel substrate using a spray gun. The thickness of the waterborne zinc-rich coating was controlled to be 50-90 µm. The sprayed coating was then dried in an oven at 40 °C for 2 hours. The lanthanide rare earth organic light-emitting material modified low surface energy coating prepared in Example 4 was sprayed onto the EGB-LDH waterborne zinc-rich coating using a spray gun. The thickness of the coating was controlled to be 50-90 µm. The sprayed coating was then dried in an oven at 40 °C for 6 hours.

[0024] A self-healing and self-early warning protective coating modified by dual doping of Ginkgo biloba extract and rare earth complex was prepared. The surface SEM morphology of the dual-doped modified self-healing and self-early warning protective coating before and after full immersion corrosion is as follows: Figure 1 As shown ( Figure 1 'a' represents the state before corrosion. Figure 1 b represents the post-corrosion state, showing the base water-based zinc-rich coating before and after full immersion corrosion. Figure 2 'a' represents the state before corrosion. Figure 2 b shows the SEM morphology of the surface after corrosion. Figure 2 As shown, the dual-doped modified self-healing and self-warning protective coating prepared by this invention has increased overall density compared to the basic water-based zinc-rich coating, and the surface defects are reduced after immersion corrosion, thus reflecting the improved corrosion resistance of the coating.

[0025] Example 6: A convenient method for identifying the degree of coating corrosion Using a handheld ultraviolet lamp, samples of the self-healing and self-early warning protective coating modified by dual doping of Ginkgo biloba extract and rare earth complex prepared in Example 5 were compared before and after service. From a macroscopic perspective, the change in fluorescence intensity was judged by human eye observation. If the fluorescence intensity decreased compared with the blank sample, it could be determined that the substrate had been corroded.

[0026] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A dual-doped modified self-healing and self-early warning protective coating, characterized in that, The coating is composed of a modified waterborne zinc-rich coating and a modified low surface energy coating. The modified waterborne zinc-rich coating is obtained by modifying the waterborne zinc-rich coating with hydrotalcite-ginkgo extract, and the modified low surface energy coating is obtained by modifying the low surface energy coating with lanthanide rare earth organic materials. The hydrotalcite-ginkgo extract is prepared by reacting ginkgo leaf extract and hydrotalcite. The lanthanide rare earth organic materials are formulated with europium nitrate hydrate, 1,10-phenanthroline, terephthalic acid, anhydrous ethanol, and deionized water. The components and contents of the modified waterborne zinc-rich coating are as follows, by weight percentage: The components and their contents in the modified low surface energy coating, by weight percentage: 。 2. The protective coating according to claim 1, characterized in that, The preparation method of the hydrotalcite-ginkgo extract is as follows: calcined hydrotalcite is added to a solution containing ginkgo extract and sodium hydroxide, the mixture is stirred and the pH of the mixture is controlled to be stable at 10.5-11.5, and the reaction is carried out at 50℃ for 15-24 hours. After filtration and washing until neutral, the hydrotalcite-ginkgo extract is obtained after drying.

3. The application of the protective coating as described in claim 1 or 2, characterized in that, Includes the following steps: 1) Apply the modified water-based zinc-rich coating to the metal substrate using a spray gun and then dry it; 2) Spray the modified low surface energy coating onto the modified water-based zinc-rich coating from step 1) that has already dried and then dry it.

4. The application of the protective coating according to claim 3, characterized in that, The coating thickness of both the modified water-based zinc-rich coating and the modified low surface energy coating is 50-90µm.

Citation Information

Patent Citations

  • Solvent type zinc-rich heavy anti-corrosion coating

    CN117070123A

  • Bi-component weather-resistant adhesive for photovoltaic back plate as well as preparation method and application of bi-component weather-resistant adhesive

    CN119371925A